Alteration of fecal microbiome and metabolome by mung bean coat improves diet-induced non-alcoholic fatty liver disease in mice - Dianzhi Hou; Jian Tang; Meili Huan; Fang Liu; Sumei Zhou; Qun Shen (Food Science and Human Wellness)
Dysbiosis of gut microbiota and its derived metabolites has been linked to the occurrence and development of nonalcoholic fatty liver disease. Our previous study has demonstrated that mung bean coat (MBC) might be mainly responsible for the beneficial effects of whole mung bean on high fat diet (HFD)-induced metabolic disorders. To investigate whether MBC, which is rich in dietary fiber and phytochemicals, can protect against HFD-induced hepatic steatosis in mice via targeting gut microbiota and its metabolites, we conducted this study. Results showed that MBC could effectively alleviative the obese phenotype, reduce the lipid accumulation and insulin resistance, and improve the hepatic oxidative stress and inflammatory response. Furthermore, MBC significantly prevented the HFD-induced changes in the structure and composition of gut microbiota, characterized by promoting the bloom of Akkermansia, Lachnospiraceae_NK4A136_group, and norank_f_Muribaculaceae, and along with the elevated short-chain fatty acids concentrations. Non-targeted metabolomic analysis indicated a metabolism disorder that was obviously improved by MBC via regulating sphingolipid metabolism and α-linolenic acid metabolism. These findings suggested that MBC could improve hepatic steatosis through manipulating the crosstalk between gut microbiota and its metabolites.